Can We Blame it on Rio? - GAFFNEY, CHRISTOPHER (Bulletin of Latin American Research, 2019)
The Rio de Janeiro Olympic Games were the last major sporting event in a decade‐long cycle in the Brazilian metropolis. In the years leading up to the Rio 2016 Summer Olympic Games, the city's urban planning agenda was captured by the exogenous demands of hosting the quadrennial spectacular. This capture has exacerbated four tendencies that will pertain in Rio de Janeiro for the foreseeable future: consolidation of consumer sovereignty, restructuring of urban circulations, financialisation of urban territories, and securitisation of exception.